Photosensitized Oxidation of 9,10-Dimethylanthracene on Dye-Doped Silica Composites - Elim Albiter; Salvador Alfaro; Miguel A. Valenzuela (International Journal of Photoenergy)
A series of cationic dyes, methylene blue (MB), safranin O (SF), toluidine blue (TB), and neutral red (NR), were successfully incorporated into a silica matrix by using ultrasound irradiation during the Stöber process. Several analyses were performed, including scanning dynamic light scattering (DLS), electron microscopy (SEM), nitrogen physisorption, FTIR spectroscopy, UV-vis, and diffuse reflectance spectroscopy. The entrapped dyes on silica were evaluated in singlet oxygen (1O2) generation under visible light irradiation, by means of the photosensitized oxidation of 9,10-dimethylanthracene (DMA). According to the results, the photocatalytic performance of the silica composites was improved, and the leakage of the dye from the particles was suppressed. Among these four different types of dye-doped silica composites, the SiO2-SF composite showed the most efficient delivery of 1O2.